2011
DOI: 10.4028/www.scientific.net/amr.217-218.439
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermal Conductivity of Compostie Particles Filled Epoxy Resin

Abstract: E-44 epoxy resin was used as matrix,and silicon nitride,boron nitride,alumina and silicon carbide were used as heat-conducting insulating fillers. By selecting the amounts and types of the insulting fillers, the heat conductive properties of E-44 could be adjusted. In addition, by choosing the curing agent and accelerator the viscosity of E-44 could also be readily controlled. The relation among the adhesive viscosity,heat conductive property and prescription was studied. When the amounts of silicon nitride, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…filled epoxy resins with BN, AlN, silicon nitride and silicon carbide. They showed that by selecting the amount and type of fillers the heat conductive properties of the epoxy composites could be adjusted; in addition, by appropriately choosing the curing agent and the accelerator, the viscosity of the medium could be readily controlled …”
Section: Introductionmentioning
confidence: 99%
“…filled epoxy resins with BN, AlN, silicon nitride and silicon carbide. They showed that by selecting the amount and type of fillers the heat conductive properties of the epoxy composites could be adjusted; in addition, by appropriately choosing the curing agent and the accelerator, the viscosity of the medium could be readily controlled …”
Section: Introductionmentioning
confidence: 99%
“…Smaller size, faster transmitting speed, and bigger storage capacity are becoming the trend for developing electric products; hence, composites with high thermal conductivity have been increasingly demanded . Many researchers have demonstrated that adding inorganic fillers with high thermal conductivity to polymers is an effective route to prepare high thermal conductive materials, but it is noteworthy that the content of inorganic fillers should be relatively high to achieve high thermal conductivity, which tends to decrease the processing characteristics and mechanical properties . Therefore, achieving high thermal conductivity by adding smaller amount of inorganic fillers to polymers is an interesting and challenging topic.…”
Section: Introductionmentioning
confidence: 99%